Wiener Jahrbuch für Kunstgeschichte Band LIX - Aurenhammer, Hans H. (2011)
Characteristic for all contributions to the Wiener Jahrbuch in 2010 is the presentation of latest research findings with the help of methodological refinements. Thus Assaf Pinkus suggests a new interdisciplinary approach for trecento painting, which brings the viewer's perceptions into an analysis of image creation. Milena Bartlová, on the other hand, addresses the little considered subject of the iconoclasm of Bohemian Hussites. An important finding is that Hussitism was unable to give up the image in its medieval function, since the printed book - which could have taken over the communicative qualities of the image - had not yet been invented. Giovan Battista Fidanza also deals with a little considered subject - namely Michelangelo as wood carver. He is able to demonstrate convincingly that Michelangelo applied prefabricated blocks of limewood in the assemblage of his wooden crucifixes. The four subsequent articles are dedicated to Baroque art. Eckhart Leuschner defines the Baroque allegory as a constant and internationally standardised deployment of formal and semantic possibilities. At the centre of Kristoffer Neville's contribution is an early version of Fischer von Erlach's Entwurff einer historischen Architectur, with the help of which the creative process of Fischer's main architectural-theoretical work is reconstructed. In the complicated memoria programme of the state sarcophagus finished for Franz Stephan and Maria Theresia in 1754 in the crypt of the Vienna Capuchin Church, Werner Telesko identifies both Antique and Christian strands of tradition. Werner Hofmann, meanwhile, recognises the 1711 endowment decree for Lothar Franz von Schönborn as an inofficial foundation source for Schloss Pommersfelden and traces a 'hypertext' within the decree, which represents the key for the building's iconography. The amateur drawings of the Habsburgs from the 19th century are comprehended by Kerstin Merkel as autonomous non-verbal sources and integrated with historical information. Iris Wien, by contrast, sets two self-portraits of Andy Wahrhol within his known oeuvre and convincingly suggests an interpretation as Medusa. In the last four contributions to the volume, the Memorabilia, important contemporary historical documents for the history of the Vienna School are published and made accessible. Alexandra Caruso edits the memoirs of Erica Tietze Conrat. The letters of Wilde, presented by Károly Kókai, provide insights into events within the circles of Vienna art history at that time. Evonne Levy publishes for the first time a selection of letters written by Hans Sedlmayr to Meyer Schapiro in the period 1930-35. Charles Hope succeeds in portraying in convincing complexity the scholarly range of Sir Ernst Gombrich.